PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN CANVA DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Elsa Febriani; Fadhilaturrahmi; Yenni Fitra Surya; Sumianto; Iis Aprinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is the low interest of students in learning mathematics in class IV. This study aims to increase interest in learning mathematics in class IV UPT SDN 010 Stabu. This research is a class action research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were 1 teacher and 25 students, while the object was to use the Application of Realistic Mathematics Education Learning Model Assisted by Canva in Increasing Interest in Learning Mathematics of Elementary School Students This research instrument consists of teacher activity observation sheets, student activią observation sheets, and questionnaire sheets While the data analysis techniques used are qualitative analysis and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, in cycle I the total score is 1,511 with 60,4% completeness in the sufficient category. In cycle II the total score was 2,029 with 81.1% completeness in the high category. Based on the results of this study, it shows that when applying the Realistic Mathematic Education Learning Model assisted by Canva, it can increase the interest in learning mathematics of class IV UPT SDN 010 Stabu students